Cyberbullying using the phenomenological approach: a systematic literature review - Lian, Tang; Siti Zobidah Omar (Penerbit Universiti Kebangsaan Malaysia, 2023)
Traditional bullying is characterized by physical, verbal, and interpersonal aggression. With the rapid development of information and communication technology, bullying has extended to cyberspace, where it is known as cyberbullying. The increasing prevalence of cyberbullying has attracted the attention of scholars around the world, and a number of researchers have employed the phenomenological approach to explore its nature. The purpose of this systematic literature review is to identify and bridge gaps in themes, data collection strategies, research subjects and regions in research on cyberbullying that adopts a phenomenological approach. The PRISMA systematic review method is adopted to review 19 papers retrieved from the Scopus, Google Scholar and Dimensions databases. Only original research journal articles and theses, which were published by the end of 2020, in English, and on cyberbullying using qualitative research method by phenomenological approach, were included in this systematic review. The Prediction Study Risk of Bias Assessment Tool (PROBAST) was adopted to appraise the quality of the reviewed articles. From the review’s quantitative and qualitative (content analysis) synthesis, eight themes, two major data collection strategies, seven groups of research subjects and six research regions emerge. The major limitation is that this study focuses on research on cyberbullying that uses the phenomenological approach, to the exclusion of other qualitative research approaches and quantitative research methods. It is recommended that future studies should broaden the parameters and scope of research on cyberbullying to pursue a more comprehensive review study.